2021
DOI: 10.1089/ast.2020.2277
|View full text |Cite
|
Sign up to set email alerts
|

Magma Ocean Evolution of the TRAPPIST-1 Planets

Abstract: Recent observations of the potentially habitable planets TRAPPIST-1 e, f, and g suggest that they possess large water mass fractions of possibly several tens of weight percent of water, even though the host star's activity should drive rapid atmospheric escape. These processes can photolyze water, generating free oxygen and possibly desiccating the planet. After the planets formed, their mantles were likely completely molten with volatiles dissolving and exsolving from the melt. To understand these planets and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 121 publications
(246 reference statements)
3
47
0
Order By: Relevance
“…The ways in which broader planetary context controls the long-term build-up of oxygen due to slight imbalances in sources and sinks is less understood. Oxygen build-up on planets around low mass stars due to extensive hydrogen escape during the pre-main sequence has been suggested 20 , and coupled models have explored whether such oxygen build-up could overwhelm magma ocean sinks 21,22,23 . The possibility of oxygen accumulation due to water loss in atmospheres with low non-condensable inventories has also been proposed 24,25 .…”
Section: Mainmentioning
confidence: 99%
“…The ways in which broader planetary context controls the long-term build-up of oxygen due to slight imbalances in sources and sinks is less understood. Oxygen build-up on planets around low mass stars due to extensive hydrogen escape during the pre-main sequence has been suggested 20 , and coupled models have explored whether such oxygen build-up could overwhelm magma ocean sinks 21,22,23 . The possibility of oxygen accumulation due to water loss in atmospheres with low non-condensable inventories has also been proposed 24,25 .…”
Section: Mainmentioning
confidence: 99%
“…to loss driven by ultraviolet radiation from the central star (especially for the inner planets). 35,36 Models of the early evolution of the Trappist-1 planets that also include the magma ocean phase 27,37 find that each planet may have lost a few to 20 Earth oceans of water. 27 Calculations that make assumptions designed to maximize water loss still find an upper limit of 25 oceans lost in the interval before planets e through h reached the habitable zone.…”
Section: Moonforming Impactmentioning
confidence: 99%
“…We used interior structure 23 and atmospheric 24 models constrained by the latest planetary mass and radius estimates. 3 Given that inferred water contents are subject to interior degeneracies, 3,[25][26][27][28] we estimated water mass fractions assuming five different rocky interior models (see Methods). Across all of our models we found that planets b, c and d are likely to be volatile-depleted whereas the outer planets (e through h) are more likely to have significant water contents (consistent with previous models 3,28 ).…”
mentioning
confidence: 99%
“…Planetary land/ ocean fractions emerge in a compromise between water's total budget and distribution between surface and interior reservoirs and the size of the basins carved out by topography (e.g., Simpson 2017). The resulting ocean mass from the former is largely stochastic: coded within it are the histories of volatile delivery during accretion (Raymond et al 2006;Morbidelli et al 2012), interior degassing from the magma ocean and succeeding mantle (Elkins-Tanton 2008; Schaefer & Fegley 2017;Katyal et al 2020;Ortenzi et al 2020;Barth et al 2021;Bower et al 2021;Guimond et al 2021;Lichtenberg et al 2021), atmospheric erosion by impacts (Zahnle & Catling 2017;Schlichting & Mukhopadhyay 2018;Howe et al 2020), and photodissociative atmospheric escape (Tian & Ida 2015;Zahnle et al 2019;Gronoff et al 2020), along with the surface temperature and pressure. In contrast, large-scale aspects of planetary topography may lend themselves to deterministic relationships with observable planetary bulk properties.…”
Section: Introductionmentioning
confidence: 99%